Frictional slip weakening and shear-enhanced crystallinity in simulated coal fault gouges at slow slip rates - C. Fan (Solid Earth, 2020)
Previous studies show that organic-rich fault patches may play an important role in promoting unstable fault slip. However, the frictional properties of rock materials with nearly 100 % organic content, e.g., coal, and the controlling microscale mechanisms remain unclear. Here, we report seven velocity stepping (VS) experiments and one slide–hold–slide (SHS) friction experiment performed on simulated fault gouges prepared from bituminous coal collected from the upper Silesian Basin of Poland. These experiments were performed at 25–45 MPa effective normal stress and 100 ∘C, employing sliding velocities of 0.1–100 µm s−1 and using a conventional triaxial apparatus plus direct shear assembly. All samples showed marked slip-weakening behavior at shear displacements beyond ∼ 1–2 mm, from a peak friction coefficient approaching ∼0.5 to (nearly) steady-state values of ∼0.3, regardless of effective normal stress or whether vacuum-dry or flooded with distilled (DI) water at 15 MPa pore fluid pressure. Analysis of both unsheared and sheared samples by means of microstructural observation, micro-area X-ray diffraction (XRD) and Raman spectroscopy suggests that the marked slip-weakening behavior can be attributed to the development of R-, B- and Y-shear bands, with internal shear-enhanced coal crystallinity development. The SHS experiment performed showed a transient peak healing (restrengthening) effect that increased with the logarithm of hold time at a linearized rate of ∼0.006. We also determined the rate dependence of steady-state friction for all VS samples using a full rate and state friction approach. This showed a transition from velocity strengthening to velocity weakening at slip velocities >1 µm s−1 in the coal sample under vacuum-dry conditions but at >10 µm s−1 in coal samples exposed to DI water at 15 MPa pore pressure. The observed behavior may be controlled by competition between dilatant granular flow and compaction enhanced by the presence of water. Together with our previous work on the frictional properties of coal–shale mixtures, our results imply that the presence of a weak, coal-dominated patch on faults that cut or smear out coal seams may promote unstable, seismogenic slip behavior, though the importance of this in enhancing either induced or natural seismicity depends on local conditions.